2017
DOI: 10.1016/j.cmi.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for screening, monitoring, prevention, prophylaxis and therapy of hepatitis B virus reactivation in patients with haematologic malignancies and patients who underwent haematologic stem cell transplantation—a position paper

Abstract: Haematologic patients should be screened for hepatitis B surface antigen (HBsAg) plus anti-hepatitis B core protein (HBc), and HBV DNA before chemotherapy. HBV DNA levels should be monitored monthly in all HBV-positive patients who do not receive prophylaxis. HBsAg-positive haematologic patients and those undergoing HSCT should receive third-generation antiviral therapy as prophylaxis. Anti-HBc-positive lymphoma patients and those receiving HSCT should receive antiviral prophylaxis. All HBV-negative haematolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 44 publications
2
96
0
1
Order By: Relevance
“…Among them, we found that 43% experienced HBV reactivation after suspending prophylaxis. This is in line with clinical cases of HBV reactivation after prophylaxis withdrawal and suggests the need to reconsider proper duration of antiviral prophylaxis particularly in onco‐haematological settings undergoing profound immunosuppression …”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Among them, we found that 43% experienced HBV reactivation after suspending prophylaxis. This is in line with clinical cases of HBV reactivation after prophylaxis withdrawal and suggests the need to reconsider proper duration of antiviral prophylaxis particularly in onco‐haematological settings undergoing profound immunosuppression …”
Section: Discussionsupporting
confidence: 55%
“…This is in line with clinical cases of HBV reactivation after prophylaxis withdrawal [10][11][12] and suggests the need to reconsider proper duration of antiviral prophylaxis particularly in onco-haematological settings undergoing profound immunosuppression. 13 We found that patients experiencing HBV reactivation after suspending antiviral prophylaxis were characterized by higher median Based on the overall findings, novel virological or immunological parameters, capable to detect also minimal HBV replication, may provide an added value in diagnosing HBV reactivation at an early stage. In this regard, a recent study has shown that positivity to HBV core-related antigen (HBcrAg) is a significant risk factor for HBV reactivation in anti-HBc-positive/HBsAg-negative patients.…”
Section: Discussionmentioning
confidence: 68%
“…All societal guidelines recommend HBV serologies with HBsAg, HBcAb, and hepatitis B surface antibody (HBsAb). Based on the serology results, an assessment of HBV DNA PCR is recommended, which can be used as a baseline for follow‐up . This strategy may miss the rare patient with occult HBV who has a low titer of HBV DNA with negative HBsAg and HBcAb serologies; therefore, in selected high‐risk patients, HBV DNA quantification should be included in the initial screening …”
Section: Who Needs To Be Screened For Hbv?mentioning
confidence: 99%
“…51 Polyomavirus and norovirus infections were defined as positive PCR from blood and disease as detection of virus by PCR or immunohistochemistry in bodily fluids or organ tissue together with symptoms and/or signs in the affected organ. 52,53 The guidelines of Sarmati et al 54 were used to identify cases of Hepatitis B infection. Acute and chronic GVHD were classified according to the Glucksberg and the National Institute of Health criteria, respectively.…”
Section: Study Definitionsmentioning
confidence: 99%